Colorimetric discrimination of tea polyphenols based on boronic acid sensor assembled with pH indicator. (July 2022) - Hu, Ying; Shao, Lixia; Fan, Yao; Lu, Lingmin; Zhou, Chunsong; Fu, Haiyan; She, Yuanbin
Abstract: Due to their analog chemical structures and trace amounts, the distinguishment of tea polyphenols has always been an important but difficult challenge. In this paper, a novel sensing strategy NapB-MR by combining boronic acid-based sensor NapB with pH indicator (methyl red, MR) was constructed to colorimetrically identify different tea polyphenols. Gallic acid (GA), methyl gallate (MG), epicatechin (EC), epicatechin gallate (ECG), epigallocatechin (EGC) and epigallocatechin gallate (EGCG) were selected as analytes, which represent the majority of the polyphenols present in green tea. Due to the pH change profile induced by boronic ester formation, methyl red was applied to reflect the difference by exhibiting a unique colorimetric response towards each tea polyphenol. In combination with the Partial Least Squares Discriminant Analysis (PLSDA) model, the discrimination of six tea polyphenols were successfully carried out. In addition, quantitatively detection of each tea polyphenol could be achieved by coupling with UV–Vis spectroscopy, and low detection limits were obtained. Most importantly, the NapB-MR was successfully applied to classify green tea samples within different categories and grades with an identification rate of 100%. Therefore, the proposed sensing strategy can be a promising method for analog detection that can meet the increasing demand from consumers for the discrimination of polyphenol-related natural products. Graphical abstract: Image 1 Highlights: A novel sensing strategy by combining boronic acid-based sensor with pH indicator was constructed for discrimination of tea polyphenols. The sensing strategy NapB-MR exhibited unique colorimetric performance towards 6 tea polyphenols, which was detectable by naked eye. NapB-MR has been successfully applied to distinguish different categories and grades of green tea with an identification rate of 100%.